Las privatizaciones de las empresas públicas en el Perú: Un enfoque económico y social - Verastegui Huanca, Lucio Leo (2018)
Objective: To analyze the neoliberal swing of the Peruvian economy from the events carried out in the Peruvian economy until the privatizations carried out in the 1990s by the government in office. Method: The research is of a documentary nature that consists in the analysis of information collected from secondary sources. At the same time, it is a descriptive investigation since it describes the process of the neoliberal turn from a Wallestenian approach. Results: There is information associated with three relevant factors of the study: a primary export insertion, the external debt and privatizations which have been analyzed using descriptive graphics. Conclusions: The insertion of Peru in the capitalist world system was as a primary exporting economy (extractivist), followed by the attempt of Industrialization by Import Substitution that brought about a great imbalance in the balance of payments and an imminent debt. Finally, after the privatizations had taken place the opening of Peruvian neoliberalism towards a model of an economy which is dependent and incapable of laying the foundations of its own development was fixed.